Pragmatic Analysis of Directives and Commisives Illocutionary Acts in Krishna's Dialogue in Little Krishna: The Terrible Storm - Das, Giridaridhari; Parthama, I Gusti Ngurah; Soethama, Putu Lirishati (LITERA : Jurnal Bahasa Dan Sastra, 2023)
This article discussed illocutionary acts that are found in Krishna's dialogues from the TV-series Little Krishna: The Terrible Storm, and the significance of context of situation in classifying the findings. The data were analyzed using the Taxonomy of Elementary Illocutionary Acts theory by JR. Searle and pragmatically analyzed using Context of Situation Theory by Halliday. The result is that, there are five directives illocutionary acts namely requestives, questions, prohibitives, permissives and advisories; and three commissives illocutionary acts namely promising, pledging and offering, found in Krishna's dialogue. Context of situation theory helped in categorizing the classification of illocutionary acts found, significantly.